(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
(7R)-trans, trans-nepetalactone; a monoterpene iridoid (1) and acetylenic compound named cis-lachnophyllum ester (2) were isolated from the essential oils of Nepeta elliptica and Erigeron annuus, respectively and characterized using a combination of their spectral dataÂ (1D-and 2D-NMR, MS, IR). Compound 1 and 2 were tested for biopesticide activity against mustard aphid, Lipaphis erysimi (Kalt.). Compound 1 exhibited high insecticidal activity towards L. erysimi with LC50 values of 2.18 and 2.73 mg/mL; LT50 values of 15.24 and 17.18 h. Compound 2 also displayed significant insecticidal activity having LC50 values of 0.85 and 4.70 mg/mL; LT50 values of 13.25 and 26.2 h. The activity of compounds 1 and 2 were comparable with synthetic pesticide, monocrotophos used as positive control and thus has potential as natural pesticides for use in economically important crops.